Chemical Disarmament: Current Problems in Implementing the Chemical Weapons Convention - Matoušek, J. (Kemija u Industriji, 2006)
The Chemical Weapons Convention (CWC) is briefly characterised by stressing its main pillars, such as verified destruction ofCWstockpiles and destruction/conversion ofCWproduction facilities (CWPFs), verified non-production of CW by the chemical industries, assistance and protection), and international cooperation. The CWC´s leading principle in defining theCW(protecting it generally against scientific and technological development, i. e. so called General Purpose Criterion) is thoroughly elucidated showing its relation to the CWC´s sophisticated verification system. Status of implementation (as of August 2005) shows main data obligatory declared by the States Parties (SP), among them 6 possessors of CW stockpiles (Russia, USA, India, South Korea, Albania and Libya). From the declared 71 373 agent-tons, 12 889 have been destroyed, from the declared 8 679 M items of munitions (containers), 2 420 have been destroyed, which means that the anticipated 10 years deadline for CW destruction (after entry into force EIF) will be not managed. For Russia and USA the allowed extension by another 5 years has been already agreed. From the 64 CWPFs (operational after 1946), declared by 12 SPs, 53 have been certified as destroyed/converted. The Organisation for the Prohibition of Chemical Weapons (OPCW) is briefly presented and main results of the First Review Conference (2003) analysed on the base of the adopted principal documents. Future problems of implementing the CWC are connected in the first line with its universality, because among 16 non-SPs, several countries (located mainly in the Near East and on the Korean peninsula) are presumed to be CW-possessors. Special emphasis is laid on both, threats and benefits of the scientific and technological development for current implementing the CWC as well as of its implementation in future after all CW stockpiles have been destroyed.